Glutathione-Related Enzyme Activity In Rat’s Testes And Epididymis At An Acute Intoxication With A Synthetic Pyrethroid Deltamethrin - E.A. CHIGRINSKI; V.D. CONWAY; L.K. GERUNOVA; T.V. GERUNOV (International Journal of Pharma and Bio Sciences, 2015)
The study was aimed for evaluation of glutathione-related enzyme activity in rats’ testes and epididymis at an acute intoxication with a deltamethrin. The study was carried out on 24 male Wistar strain rats of body weight 240±10g arranged into 2 groups – control and test ones each of 12 specimens. The test group was exposed to an acute deltamethrin intoxication in a dose of 43.5 mg/kg per body wt. The acute deltamethrin intoxication is accompanied by the accumulation of uric acid and malondialdehyde associated with the lowering of glutathione level and glutathione peroxidase, glutathione reductase, glutathione S-transferase and gamma-glutamyl transferase activation in the testes and epididymis of rats. Activation of glutathione-related enzymes in the reproductive organs of rats exposed to an acute deltamethrin intoxication was due to the activation of free radical processes caused by the intensification of purine catabolism.